Case report: First documented case of cerebral angiostrongyliasis caused by Angiostrongylus costaricensis in a free-ranging opossum - Solorzano-Scott, Tamara; Aguilar-Vargas, Fernando; Cordero-Salas, Martha; Conejo, Amanda; Rojas, Alicia; Baldi, Mario (Frontiers in Veterinary Science, 2024)
Angiostrongylus costaricensis is a metastrongyloid nematode that primarily infects the mesenteric arteries of wild rodents. This parasite is endemic in several regions of the American continent, and in humans, causes a disease known as abdominal angiostrongyliasis. Despite the important health implications of this nematode, there are limited studies investigating the involvement of wild animals in its life cycle. In this study, we present the clinical manifestations, pathologic findings, and molecular diagnosis, to the best of our current knowledge, of the first documented onset of cerebral angiostrongyliasis because of A. costaricensis infection in a juvenile free-ranging opossum (Didelphis marsupialis). Histopathological findings stress the presence of eosinophilic meningoencephalitis with nematodes present within the lesions, and PCR was positive for cox1 and ITS1 reactions. The obtained sequences for a 279 bp fragment of ITS1 were 100% identical to A. costaricensis from Costa Rica. This case highlights the substantial difficulties in diagnosing neuroangiostrongyliasis, yet underscores the importance of considering A. costaricensis as a potential culprit behind neurological conditions in wild marsupials. It acts as an urgent call to action to improve surveillance programs tracking infectious and parasitic diseases causing mortality in wildlife populations.